Pemanfaatan Mikrotik Dalam Manajemen Bandwidth Pada Jaringan Sekolah - Fauzan Prasetyo Eka Putra; Debri Eko Arissandi; Achmad Rofiqi; Moh Firman Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
The preparation of this research is intended as an effort of Mikrotik in bandwidth management on school networks to improve the stability and efficiency of internet access in an educational environment. The main problem faced by schools is the imbalance of bandwidth distribution and the use of networks for non-educative activities. The research uses a qualitative descriptive approach with a few hands-on configuration experiments on Mikrotik RouterBoard devices. The results show that the Simple Queue, Queue Tree, and Layer 7 Protocol features successfully divide bandwidth proportionally based on user categories (teachers, students, and guests), block access to irrelevant sites, and increase connection sta-bility by 90%. Real-time network monitoring also enables more effective control and evaluation. However, it requires certain technical expertise and a regular maintenance system to maintain optimal performance. This research recommends further development in more complex networks and integra-tion with more advanced security systems. Overall, Mikrotik is an effective and economical bandwidth management solution for school environments.